2020
DOI: 10.1111/avsc.12481
|View full text |Cite
|
Sign up to set email alerts
|

Establishment dynamics of native and exotic plants after disturbance along roadsides

Abstract: Questions How does small‐scale soil disturbance influence establishment dynamics of native and exotic species along roadsides? Does soil disturbance provide potential opportunities to exotic invasions along elevational gradients? Does the established plant community after disturbance reflect the surrounding vegetation? Location Prealps, Italy. Methods To disentangle the role of elevation and soil disturbance in promoting exotic invasions, we performed a manipulative experiment along 12 roads spanning an elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Alien species richness peaked at the lowest elevations, where human impact is stronger and human population density is higher. Currently, the greatest number of alien species in the world and the greatest knowledge about the extent of invasions are reported in economically developed countries (Pyšek et al 2008, McGeoch et al 2010, Early et al 2016, Corcos et al 2020. Due to an interplay between climate warming and direct human impact, an upward shift of the alien species is expected in the near future (Walther et al 2009, Alexander andEdwards 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Alien species richness peaked at the lowest elevations, where human impact is stronger and human population density is higher. Currently, the greatest number of alien species in the world and the greatest knowledge about the extent of invasions are reported in economically developed countries (Pyšek et al 2008, McGeoch et al 2010, Early et al 2016, Corcos et al 2020. Due to an interplay between climate warming and direct human impact, an upward shift of the alien species is expected in the near future (Walther et al 2009, Alexander andEdwards 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the effect on species richness, soil disturbance has been identified as a key driver of plant community composition (Corcos et al, 2020; Haider et al, 2018). Beta‐diversity between disturbed and resident vegetation was high, indicating that a large proportion of established species did not occur in the surrounding vegetation but only in the seed‐bank (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, soil disturbance related to the construction of roads, ski‐slopes and other infrastructures has become more frequent across temperate mountain ecosystems (Wipf et al, 2005). Disturbance (through the removal of existing vegetation) decreases competition for light and increases the chances of seed germination and establishment of ruderal plants and species present only in the seed‐bank (Corcos et al, 2020; Haeuser et al, 2017; Lembrechts et al, 2017; McDougall et al, 2018). Besides the direct effects on plants, disturbance also affects key soil properties such as nutrient and water content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of floristic composition in the north of Argentine Patagonia, carried out on a west-east precipitation gradient that included areas of forest, shrubland and steppe, revealed that the shrubland and steppe had the highest presence of exotic species, the most frequent being Bromus tectorum, Cerastium arvense and Rumex acetosella [36]. A large number of studies in the world have assessed the influence of roads on exotic plant dispersal and establishment in aboveground vegetation [9,11,13,37,38], but soil seed bank on roadsides have been less examined [27,39]. In particular these topics have been under-researched in Patagonian steppe roadsides [26,40].…”
Section: Introductionmentioning
confidence: 99%